A666-conjugated nanoparticles target prestin of outer hair cells preventing cisplatin-induced hearing loss - Wang XL (Dove Medical Press, 2018)
Xueling Wang,1–3,* Yuming Chen,1–3,* Yong Tao,1–3 Yunge Gao,1–3 Dehong Yu,1–3 Hao Wu1–3 1Department of Otolaryngology-Head and Neck Surgery, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Ear Institute, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Shanghai Key Laboratory of Translational Medicine on Ear and Nose Diseases, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: The delivery of treatment agents to inner ear with drug delivery system (DDS) has been under investigation to overcome the limitations of the conventional therapeutic agents in curing or alleviating the cisplatin ototoxicity.Methods: In the present study, a novel targeted dexamethasone (DEX)-loaded DDS, A666-DEX-NP, was constructed for prevention from cisplatin-induced hearing loss. A666-(CLEPRWGFGWWLH) peptides specifically bind to prestin, which is limited to the outer hair cells (OHCs). HEI-OC1 and cisplatin-treated guinea pigs (12 mg/kg, intraperitoneal) were used as in vitro and in vivo models for investigating the targeting and protective efficiency against cisplatin.Results: As expected, compared to A666-unconjugated nanoparticles (NP), A666-conjugated coumarin 6-labeled NP showed active targeting to OHCs. Furthermore, A666-coumarin 6-labeled NP could be significantly internalized by HEI-OC1 cells via the A666–prestin interaction. This facilitated the uptake of cells pretreated with A666-DEX-NP, followed by the cisplatin-treated group, which led to enhanced cell viability, reduced apoptotic properties, and decreased reactive oxygen species levels as compared to cells pretreated with DEX or DEX-NP, 4 hours in advance of cisplatin treatment. In cisplatin-treated guinea pigs, pretreatment with A666-DEX-NP effectively preserved OHCs and showed significant hearing protection at 4, 8, and 16 kHz as compared to pretreatment with saline, DEX, or DEX-NP formulation.Conclusion: This OHC-targeting DDS provides a novel strategy for DEX application that can be potentially used to combat cisplatin ototoxicity. Keywords: A666 peptide, dexamethasone, prestin, cisplatin ototoxicity